1997
DOI: 10.1207/s15328015tlm0904_1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Student Performance in Combined Baccalaureate-MD Degree Programs

Abstract: The support systems of the Baccalaureate-MD degree programs facilitate retention in a medical career. The educational experiment of the combined-degree programs has demonstrated that future physicians can be successfully selected from high school.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…Of these 32 studies, 17 were excluded for using either unwanted outcomes or outcomes defined in such a way that dropout was typically contaminated by delay in study 43–59 . Seven studies were excluded for proving irrelevant to our research question on closer inspection, 60–66 two for representing duplicate publications, 67,68 three for representing non‐primary studies, 69–71 two for examining irrelevant populations, 72,73 and one for being unpublished 74 . In addition, an ancestry search of all 69 studies referred for quality assessment resulted in the inclusion of a further 11 relevant studies 75–85 .…”
Section: Resultsmentioning
confidence: 99%
“…Of these 32 studies, 17 were excluded for using either unwanted outcomes or outcomes defined in such a way that dropout was typically contaminated by delay in study 43–59 . Seven studies were excluded for proving irrelevant to our research question on closer inspection, 60–66 two for representing duplicate publications, 67,68 three for representing non‐primary studies, 69–71 two for examining irrelevant populations, 72,73 and one for being unpublished 74 . In addition, an ancestry search of all 69 studies referred for quality assessment resulted in the inclusion of a further 11 relevant studies 75–85 .…”
Section: Resultsmentioning
confidence: 99%
“…The 1960s also saw a trend toward larger medical school class sizes. For example, between 1960 and 1970, the University of Minnesota Medical School increased its freshman class from 164 to 227 students [15]. …”
Section: Detailed Historymentioning
confidence: 99%
“…One recent study of seven combined baccalaureate/MD programs observed no apparent difference in the medical school grades or licensing examination scores the baccalaureate/MD students obtained relative to the scores obtained by students who had taken the TPM. 13 Another study observed no difference in academic performance between students in the Early Assurance Program at the Icahn School of Medicine at Mount Sinai and those admitted to the same institution through the TPM. 14 Drees et al 15 concluded that graduates of the combined baccalaureate/MD program at the University of Missouri-Kansas City outperformed students who had taken the TPM in areas such as problem solving and professionalism.…”
Section: Discussionmentioning
confidence: 97%